Stochastic Orders of Proposing Players in Bargaining - Harold Houba (Tinbergen Institute, 2005)
The bargaining model with stochastic order of proposing players is properly embedded in continuous time and it is strategically equivalent to the alternating offers model. For all parameter values, the pair of equilibrium proposals corresponds to the Nash bargaining solution of a modified bargaining problem and the Maximum Theorem implies convergence to the Nash bargaining solution when time between proposals vanishes. The model unifies alternating offers, one-sided offers and random proposers. Only continuous-time Markov processes are firmly rooted in probability theory and offer fundamentally different limit results.
Keywords: C72; C73; C78; 330; Bargaining; Negotiation; Alternating offers; Markov process; subgame perfect equilibrium; Nash bargaining solution; Maximum Theorem; Verhandlungstheorie; Dynamisches Spiel; Markovscher Prozess; Nash-Gleichgewicht; Theorie; Nichtkooperatives Spiel